The ideology of translators in Quranic translation: lessons learned from Indonesia - Fahmi Gunawan (Cogent Arts & Humanities, 2022)
Albeit research into Qur’an translation has been widely undertaken, little empirical research reports on the ideology of translators, particularly from the translation technique perspective. This research, therefore, aims at exploring the representation of the ideology of Qur’an Translators in Indonesia. The present critical translation case study design used the Qur’an translation produced by The Ministry of Religious Affairs (official) and Muhammad Thalib (unofficial) as the data source. To analyze the data, this research adopted theories from Molina and Albir, Leuven-Zwart, and Nord. The findings indicate that the practice of Qur’an translation in Indonesia was subjective, ideological, and reader-driven. The translation works from the official representative were based on moderate Islamic practices, while the unofficial one was found to contain transnational Islamic ideology. Translators’ ideology can be traced through translation techniques and translators’ backgrounds. This research suggests that the Quranic translation can be undertaken across languages because, in addition to making the text arbitrary, it also has a certain religious ideology in line with the interests and socio-cultural-political background of the translator and the target reader.